Thought Experiments between Theology, Empirical Science, and Fictional Narrative - Buzzoni, Marco (Religions, 2019)
Starting from Fehige's and Polkinghorne's analyses of the analogies between theological and scientific thought experiments (TEs), the main aim of this paper is to clarify the distinctive character of theological TEs. For this purpose, we shall compare theological TEs with empirical and, although only in passing, with narrative TEs. In order to facilitate the comparison between scientific and theological TEs, the first part of the paper provides a brief outline of an account regarding TEs in the empirical sciences from the viewpoint of a functional, not material, a priori, which is in line with, if not the full letter, the spirit of Kant's a priori. On the basis of this view, we shall investigate the most important difference (which is the source of many others) between theological and empirical TEs. In spite of the many similarities, the most important difference between empirical and theological TEs lies in the fact that theological TEs consider both empirical-descriptive and moral-normative contents from the point of view of a search for an absolute meaning beyond all relative and finite meanings. If we-developing a suggestion by Ernst Troeltsch-interpret this claim from the point of view of a purely functional "religious a priori", we may conclude that theological TEs, which express a search for an absolute meaning, do not possess a priori contents, not even moral.